Sistem Pemantauan Detak Jantung Menggunakan Sensor 3 Lead Elektrodes Berbasis Program Labview. - Angga Pratama; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This research developed a heart rate monitoring system using 3 lead elektrodes sensor based labview. Labview software used to display information generate in the form of GUI (Graphical User Interface). Hardware used is mega 2560 microcontroller arduino, signal conditioning board AD8232, and type electrode leads flops as a heart rate signal. GUI (Graphical User Interface) designed in labview provide information such as heart rate per minute, heart rate signal and heart rate characteristics such as bradycardia, tachycardia, and normal.Keywords: 3 Lead ECG, GUI (Graphical User Interface) Labview, Arduino, AD8232, Heart rate characteristics